Type 3 innate lymphoid cells producing IL-17 and IL-22 are expanded in the gut, in the peripheral blood, synovial fluid and bone marrow of patients with ankylosing spondylitis. Issue 9 (22nd April 2015) - Ciccia, Francesco; Guggino, Giuliana; Rizzo, Aroldo; Saieva, Laura; Peralta, Sergio; Giardina, AnnaRita; Cannizzaro, Alessandra; Sireci, Guido; De Leo, Giacomo; Alessandro, Riccardo; Triolo, Giovanni
Abstract : Background: The aim of the study was to better characterise the immunological origin and the behaviour of interleukin (IL)-23-responsive innate lymphoid cells (ILCs) in the gut, synovial fluid (SF) and bone marrow (BM) of patients with ankylosing spondylitis (AS). Methods: ILC1, ILC2 and ILC3 cells were determined and characterised by confocal microscopy and flow cytometry in ileal and BM biopsies, in peripheral blood (PB) and SF mononuclear cells obtained from patients with AS and controls. Mucosal vascular addressin cell adhesion molecule 1 (MADCAM-1), IL-7, IL-15 and aggregates of lymphoid tissue inducer cells (LTi) were evaluated by immunohistochemistry. The in vitro ability of epithelial cells in driving the differentiation of ILC3 and the effect of tumour necrosis factor inhibitors (TNFi) on the frequency of ILC3 and the expression of MADCAM1 were also assessed. Results: ILC3 characterised as Lyn − RORc − Tbet + NKp44 + cells were significantly expanded in the gut, SF and BM of patients with AS compared with controls, produced high levels of IL-17 and IL-22 and expressed α4β7. MADcAM1 was overexpressed in BM and ileal high endothelial venules. IL-7 was significantly increased in AS gut, especially in the context of Paneth cells, and accompanied by the presence of aggregates of c-kit/IL-7R + cells (LTi). In in vitro experiments, epithelial cells from patients with AS actively induced differentiation of ILC3 from LTi. TNFi efficacy was accompanied by a significant decrease in the percentage of intestinal and circulating ILC3 and in the expression of MADCAM1. Conclusions: Gut-derived IL-17 + and IL-22 + ILC3 are expanded in the peripheral blood, SF and inflamed BM of patients with AS, suggesting the presence of an active homing axis between the gut and the inflamed sacroiliac joints.